2021
DOI: 10.2807/1560-7917.es.2021.26.1.2002023
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring shows substantial excess all-cause mortality during second wave of COVID-19 in Europe, October to December 2020

Abstract: The European monitoring of excess mortality for public health action (EuroMOMO) network monitors weekly excess all-cause mortality in 27 European countries or subnational areas. During the first wave of the coronavirus disease (COVID-19) pandemic in Europe in spring 2020, several countries experienced extraordinarily high levels of excess mortality. Europe is currently seeing another upsurge in COVID-19 cases, and EuroMOMO is again witnessing a substantial excess all-cause mortality attributable to COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 10 publications
2
45
0
4
Order By: Relevance
“…Europe has experienced a second wave of the COVID-19 pandemic [ 19 ]. Strict social distancing measures have proven effective in curbing the incidence of COVID-19, but as restrictions were lifted, emerging second-wave scenarios [ 20 ] forced restrictive measures to be reimposed to prevent the collapse of the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Europe has experienced a second wave of the COVID-19 pandemic [ 19 ]. Strict social distancing measures have proven effective in curbing the incidence of COVID-19, but as restrictions were lifted, emerging second-wave scenarios [ 20 ] forced restrictive measures to be reimposed to prevent the collapse of the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…A ligeira mudança do perfil dos infectados com um aumento proporcional da contribuição de indivíduos de raça/cor branca (11% na segunda onda) pode ser reflexo das desigualdades no acesso aos serviços de saúde entre brancos, pardos e negros [24][25][26] . Embora a pandemia afete a população do país como um todo, seus impactos podem ser diferentes por conta das desigualdades que enfrentamos devido ao racismo estrutural e a situações de exclusão social que fazem parte da nossa realidade.…”
Section: Resultsunclassified
“…The SARS-COV-2 virus was only identified in December 2019, and access to high-quality data with sufficient detail in such a short time is limited. Some studies reported on all-cause mortality, [3,19] in relation to COVID-19 and infection control measures, but data on specific causes of death is usually lacking.…”
Section: Discussionmentioning
confidence: 99%